Localization and Imaging of Integrated Circuit Defect Using Simple Optical Feedback Detection - Cemine, Vernon Julius; Buenaobra, Bernardino; Blanca, Carlo Mar; Saloma, Caesar (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
High-contrast microscopy of semiconductor and metal edifices in integrated circuits is demonstrated by combining laser-scanning confocal reflectance microscopy, one-photon optical-beam-induced current (1P-OBIC) imaging, and optical feedback detection via a commercially available semiconductor laser that also serves as the excitation source. The confocal microscope has a compact in-line arrangement with no external photodetector. Confocal and 1P-OBIC images are obtained simultaneously from the same focused beam that is scanned across the sample plane. Image pairs are processed to generate exclusive high-contrast distributions of the semiconductor, metal, and dielectric sites in a GaAs photodiode array sample. The method is then utilized to demonstrate defect localization and imaging in an integrated circuit.